Comparison between desferrioxamine and combined therapy with desferrioxamine and deferiprone in iron overloaded thalassaemia patients - Mourad, Fadi H. (2003)
Summary. Desferrioxamine (DFX) alone (40–50 mg/kg/d s.c. over 8–12 h, five times weekly) was compared with combined DFX twice weekly and deferiprone (75 mg/kg/d) over 12 months in previously poorly chelated thalassaemia patients. Serum ferritin fell from 5506 ± 635 µg/l (mean ± SEM) to 3998 ± 604 µg/l (P < 0·001; n = 14) in the DFX group and from 4153 ± 517 µg/l to 2805 ± 327 µg/l in the combined group (P < 0·01; n = 11). Deferiprone plus DFX produced a greater mean urine iron excretion (1·01 mg/kg/24 h) than iron intake from blood transfusion in each patient. Main side-effects were skin reactions (DFX alone), nausea and arthralgia (combined therapy). As chelation therapy, the combined protocol was as effective as DFX five times weekly.